Implementasi Hukum Adat dalam Tradisi Kelahiran di Kampung Adat Mahmud, Kabupaten Bandung - Rizqullah, Muhammad Syafiq; Daffa Thabyna Innaya, Mochamad; Bassica Arvensis, Rizki; Putri Fadhilah, Najwa; Fauziyyah Kurnia, Resty; Aprilia, Eka; Faza Muafi, Haifa; Ikhsan Priyadi, Muhammad (Jurnal Pengembangan Budaya Hukum, 2026)
This study is motivated by the importance of understanding customary law practices as part of Indonesian society that continue to exist amid modernization. The focus of this research is the birth tradition in Kampung Adat Mahmud, Bandung Regency, which reflects the integration of local customary values and Islamic teachings. This study aims to analyze how the community practices, maintains, and adapts birth traditions within the framework of customary law. The research employs a qualitative method with a descriptive approach within an empirical (sociological) legal framework, using interviews and literature review as data collection techniques. The findings show that birth is not merely understood as a biological event, but also as a social and spiritual event manifested through a series of rituals from pregnancy to post-birth stages. The roles of paraji (traditional birth attendants), customary leaders, family, and religious teachers are significant in sustaining these values. Furthermore, the study reveals social recognition of children's rights and status, as well as a complementary relationship between customary law and national law. These findings highlight that customary law remains relevant as a living system that contributes to shaping social identity and community well-being. Therefore, the preservation of such traditions should be sustained while accommodating modern developments and formal legal systems.